Tác động của hoạt động phát triển bền vững đến hiệu quả tài chính của các doanh nghiệp Đông Nam Á: Vai trò của mức độ cạnh tranh thị trường - Hồ Thị Hải, Ly (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This study investigates the relationship between corporate sustainability and financial performance of firms operating in Southeast Asian countries, especially focusing on the impact of market competition. Using a comprehensive dataset during period of 2004–2019, the study suggests that in ASEAN countries, firms with superior sustainability have higher financial performance. Interestingly, this positive association is only statistically significant for firms operating in markets with high competition, however, it is not significant for firms operating in markets with low competition. The results are robust with alternative measures of corporate financial performance and alternative econometric methods.